Antitumor activity of selenium compounds and its underlying mechanism in human oral squamous cell carcinoma cells: A preliminary study. Issue 1 (January 2017) - Endo, Manabu; Hasegawa, Hiroshi; Kaneko, Tetsuharu; Kanno, Chihiro; Monma, Tsutomu; Kano, Makoto; Shinohara, Fumiaki; Takahashi, Tetsu
Abstract: Objective: Oral cancer is an aggressive disease that infiltrates the adjacent tissues and frequently metastasizes to lymph nodes in the neck. Currently, no chemotherapy effectively prevents its metastasis. Selenium compounds have been recently scrutinized as chemotherapeutic agents for various cancers. In this study, we aimed to investigate the antitumor activity of selenium compounds and elucidate the underlying inhibitory mechanism of these agents in oral cancer cells. Methods: The growth inhibitory effects of selenium compounds (sodium selenite, selenomethionine, and Se-methylselenocysteine) on human oral squamous cell carcinoma (HOSCC) cell lines (HSC-3, HSC-4, and SAS) were evaluated by MTT assay. Selenite-induced apoptosis, caspase activity, and endoplasmic reticulum (ER) stress in HSC-3 cells were evaluated by flow cytometry and western blot. Effects of selenite on Akt expression in HSC-3 cells were evaluated by ELISA and western blot. Results: Selenium compounds significantly inhibited cell growth and induced apoptosis in HOSCC cell lines. HSC-3 cells, in particular, were highly sensitive to selenite. In selenite-treated HSC-3 cells, caspase-3, 8, and 9 were conspicuously activated; pretreatment with pan-caspase inhibitor or caspase-12 inhibitor dramatically reduced selenite-induced apoptosis; ER stress markers, caspase-12 and eIF-2α, were highly activated, but Akt activation in the Akt/phosphoinositide-3-kinase pathway was downregulated. Conclusion: Our findings indicate that selenite induces apoptosis in HOSCC cell lines in a caspase-dependent manner through mitochondrial, death-receptor, and ER stress pathways. In addition, selenite could exhibit antitumor activity by downregulating Akt activation, which plays an important role in cell growth and chemotherapy resistance.